2020
DOI: 10.1007/s10661-020-8118-4
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of a low-cost sensor in the monitoring of particulate matter in Santiago, Chile

Abstract: Integration of low-cost air quality sensors with the internet of things (IoT) has become a feasible approach towards the development of smart cities. Several studies have assessed the performance of low-cost air quality sensors by comparing their measurements with reference instruments. We examined the performance of a low-cost IoT particulate matter (PM 10 and PM 2.5 ) sensor in the urban environment of Santiago, Chile. The prototype was assembled from a PM 10 -PM 2.5 sensor (SDS011), a temperature and relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 45 publications
4
54
0
5
Order By: Relevance
“…Karagulian et al [29] reviewed 110 on-site calibrated and uncalibrated LCAQMDs and concluded that most of them, including the AQY device, underestimate the PM10 hourly concentrations, which is in accordance with our results. Another study [30] evaluated a stand-alone SDS011 sensor (during winter and spring), which is used by the AQY device enhanced with RH corrections, in Santiago, Chile, with similar meteorological conditions as Thessaloniki, and found R 2 in the range (0.24-0.56) for PM10 concentrations against a similar β-attenuation reference instrument. They concluded that the sensor is suitable for monitoring PM2.5 daily levels after RH corrections, but not for PM10 levels.…”
Section: Exploratory Data Analysis (Eda)mentioning
confidence: 99%
“…Karagulian et al [29] reviewed 110 on-site calibrated and uncalibrated LCAQMDs and concluded that most of them, including the AQY device, underestimate the PM10 hourly concentrations, which is in accordance with our results. Another study [30] evaluated a stand-alone SDS011 sensor (during winter and spring), which is used by the AQY device enhanced with RH corrections, in Santiago, Chile, with similar meteorological conditions as Thessaloniki, and found R 2 in the range (0.24-0.56) for PM10 concentrations against a similar β-attenuation reference instrument. They concluded that the sensor is suitable for monitoring PM2.5 daily levels after RH corrections, but not for PM10 levels.…”
Section: Exploratory Data Analysis (Eda)mentioning
confidence: 99%
“…The number of particles is then converted to the PM mass concentration. The error occurs because the low-cost PM sensor counts not only the dry particles but also the wet water droplets that can happen at high levels of relative humidity and occur through condensation of the water vapor [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These analyzers have gone through strict field evaluations and demonstrated that they could provide concentration measures equivalent to the filter-based GMM, with the advantage of being usable for continuous PM monitoring (generally with a temporal resolution of 1 h) [5]. Finally, the optical sensors measure particles' size by light scattering, so the concentration of PM can be detected according to the signal [3,6,7]. The optical sensor's accuracy is affected by different factors, such as aerosol characteristics, temperature, humidity, and even seasonal types [3].…”
Section: Introductionmentioning
confidence: 99%